Keuangan Islam sebagai Katalisator Green Economy: Menuju Pencapaian SDGs dalam Kerangka Maqashid Syariah - A’ini, Huril; Ayu, Intan; Maghfiroh, Rizka Amaliyah (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2024)
Climate change and social inequality require sustainable solutions, one of which is through a green economy. Islamic finance has significant potential as a catalyst in supporting the implementation of a green economy oriented toward environmental sustainability and social welfare. With its Shariah principles, such as justice, sustainability, and social responsibility, Islamic finance can contribute to achieving the Sustainable Development Goals (SDGs). This study explores the role of Islamic financial instruments, such as green sukuk, zakat, waqf, and Shariah-based investments, in supporting environmentally friendly projects and community economic empowerment. This research aims to analyze the role of Islamic finance in supporting a green economy based on maqashid sharia. The method used in this research is a qualitative approach involving the study of literature, books and sources from the internet. The research results show that instruments such as green sukuk, zakat, and waqf can be used to fund environmentally friendly projects. In addition, Maqashid sharia serves as an ethical foundation that strengthens the commitment to social and environmental sustainability in the implementation of Islamic finance. With these principles, Islamic finance has the capacity to become a key driver in achieving the SDGs within the framework of sustainable development. In conclusion, the collaboration between Islamic finance and the green economy not only provides innovative solutions to the challenges of climate change and social inequality but also reinforces sharia values in supporting the well-being of society.